Empirical Research on the Latent Factors that Facilitate the Individuals’ Interaction with the Community - Cristina State, Ion Tudor; Nicolae, Valentina (European Journal of Sustainable Development, 2019)
The communion of interests and the open, voluntary membership which characterise social economy enterprises are a challenge we will be trying to deal with in this paper. Our dilemma regarding the existence of some conditionality between the individuals’ expectations from their community and their availability to get involved in solving community problems has become the main objective of the study. Solving this dilemma came as a natural consequence of the initiation of a questionnaire-based study, including separate sets of questions concerning the perception of the participants about how the community meets their expectations, combined with questions about their availability to act to the benefit of the community. The work hypotheses were tested with the IBM Statistics and Microsoft Excel applications. The results obtained after testing the hypotheses signal two important aspects: on the one hand, the availability of the participants in the study to act for the benefit of their communities is not conditional on the expectations they have from the community and, on the other hand, at the time of the survey, the preference of the study participants to act for the benefit of the community is not sufficiently well defined. Keywords: communities, social economic enterprise, solidarity, social implication